Analysis Of the Implementation of Social Reintegration In Correctional Services Based On Law Number 22 Of 2022 At The Pangkalpinang Special Development Institution For Grade II Children - I Wayan Teguh Subarata; Yandi; Junaidi Abdillah (Faculty of Law, Universitas Pekalongan, 2023)
The Correctional Service has established various policies and regulations to regulate the running of the correctional system that focuses more on fostering and social reintegration, especially for children who are facing the law. The purpose of this study is to analyze the implementation of social reintegration in LPKA Class II Pangkalpinang, based on Law Number 22 of 2022, with a focus on the factors that affect the success and challenges faced in the social reintegration process for children facing the law. This research method uses a qualitative approach with the type of case study research. The results of this study show that the implementation of social reintegration in LPKA Class II Pangkalpinang still faces various challenges that affect its success. One of the main factors found is the limited facilities that support the development of children who are facing the law. Based on the data, only 30% of children get full access to adequate practical skills training and psychological coaching. In addition, the shortage of trained educators and supervisors has also worsened the effectiveness of the reintegration program. Only 40% of respondents stated that the supervisors at LPKA have enough skills to provide comprehensive assistance, both in educational and psychological aspects. Without any improvement in this regard, the social reintegration of newly freed children will remain limited. In addition, external factors such as social stigma and lack of support from the community and family are also significant obstacles. Based on a survey of the community around LPKA, only 20% of the community showed an open attitude and supported the social reintegration of children after they were released